Size dependent melting of Silicon nanoparticles - Hang, Nguyen Thi Thuy (Communications in Physics, 2014)
Melting of crystalline silicon nanoparticles is studied by molecular dynamics (MD) simulations using Stillinger-Weber potential. Models are heated up from a crystalline to a normal liquid state. Temperature dependence of total energy and the Lindemann ratio exhibit a first-order-like behavior of the transition at the melting point. Heat capacity of the system presents a single peak at around the melting point. The size dependent melting is presented. As the size of the nanoparticles increases, the variation of the melting point becomes more monotonic and the temperature range of bistability shifts to higher temperatures. In large nanoparticles, the proportion of interior atoms increases and the average potential energy per atom converges to the bulk or thin films.